Preterm Labour: An insights into Vaginal Infections - Najma Bibi, Rubina Baber, Nayar Latif, Faryal Shah, Sobia Ahmad, Rida Naz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Preterm births result from preterm labour. The chief causes of new-born neurological morbidity and transience are prematurity and low birth weight. Vaginal infections are considered as a higher risk factor for pre term labour. Preterm labour is less common when proper antenatal examination, screening for lower urogenital tract infections, and early treatment are carried out. Methods: Group B streptococcus (GBS), Urea plasma urealyticum, Mycoplasma genitalium, Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, Treponema pallidum, bacterial vaginosis, herpes simplex virus (HSV) I and II, were all examined in vaginal swab samples from A control group of 81 expectant mothers underwent a GBS test. Tests for the antimicrobial propensities of GBS, U. urealyticum and M. hominis were conducted. Results: 8.70% of PTL-WO, 16.33% of S-PTB, 11.70% of M-PTB, and 17.29% of the control group had GBS. 13.04% of PTL-WO, 18.37% of S-PTB, and 17.65% of M-PTB had M. hominis. U. urealyticum was detected by PCR and culture in 52.17 percent of PTL-WO, 48.98 percent of S-PTB, and 55.88 percent of M-PTB. 17.39% of PTL-WO patients, 4.08% of S-PTB patients, and 5.88% of M-PTB patients had C. trachomatis. Monilia was found in 4.3% of PTL-WO, 6.12% of S-PTB, and 5.88% of M-PTB. This examination failed to discover N. gonorrhoeae, M. genitalium, HSV I, T. vaginalis, or T. pallidum; no additional bacteria or viruses were detected either. Conclusions: Lower urogenital tract infections in pregnant women should be tested for, especially in high-risk situations. When genitourinary infections are detected early and treated fast, prematurity-related infant morbidity and mortality are decreased, and preterm labour is less common. Keywords: Preterm labour, Urinary tract infection, vaginal infections